(untitled) (International Current Pharmaceutical Journal, 2016)
Objective of the present work is to develop and validate a simple, cost effective, sensitive and fast HPLC method for the analysis of Secnidazole. A Shimadzu HPLC system with Luna 5µm C18 column is employed for the analysis using Methanol:H2O (60:40, v/v) as mobile phase. Signal from Secnidazole is detected at 310nm by UV Spectrophotometer. The proposed method is fully validated and found to be linear over a workable drug concentration, accurate, precise and robust. This fast and inexpensive method is suitable for research laboratories as well as for quality control analysis in pharmaceutical industries. Sharmin et al., International Current Pharmaceutical Journal, March 2016, 5(4): 41-44 http://www.icpjonline.com/documents/Vol5Issue4/03.pdf